2017
DOI: 10.1038/ja.2017.103
|View full text |Cite
|
Sign up to set email alerts
|

Wakodecalines A and B, new decaline metabolites isolated from a fungus Pyrenochaetopsis sp. RK10-F058

Abstract: Two new decaline metabolites, wakodecalines A and B, were isolated from a fungus, Pyrenochaetopsis sp. RK10-F058, by screening for structurally unique metabolites using LC/MS analysis. Their structures were determined on the basis of NMR and mass spectrometric measurements. The absolute structures were confirmed by a combination of chemical methods including chemical degradation, a modified Mosher's method and Marfey's method, and comparison of the experimental electronic CD (ECD) spectrum with calculated one.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…To this end, we searched for fungal strains that produce metabolites containing a decalin that is enantiomerically opposite to that of 1 and found a phomasetin ( 2 )‐producing fungus, Pyrenochaetopsis sp. RK10‐F058 . It should be noted that, although all the stereocenters of 2 are opposite to those of 1 , they have been reported as an HIV‐1 integrase inhibitors .…”
Section: Figurementioning
confidence: 99%
“…To this end, we searched for fungal strains that produce metabolites containing a decalin that is enantiomerically opposite to that of 1 and found a phomasetin ( 2 )‐producing fungus, Pyrenochaetopsis sp. RK10‐F058 . It should be noted that, although all the stereocenters of 2 are opposite to those of 1 , they have been reported as an HIV‐1 integrase inhibitors .…”
Section: Figurementioning
confidence: 99%
“…It seems that the configuration at C-5 has strong correlation with the larvicidal activities, as the epimer of 1 (i.e., 2) was two times less active than that of 1. Decalin-type tetramic acid metabolites were found to display diverse activities, such as HIV-1 integrase inhibiting activity [19], antibacterial activity [18,[20][21][22], antimalarial activity [23] and anti-parasite activity against Trichomonas vaginalis [24]. Our research revealed these type of compounds also have larvicidal function.…”
Section: Larvicidal Activitiesmentioning
confidence: 69%
“…To our knowledge, the very first chemical study was published in 2017 by Nogawa et al on a Pyrenochaetopsis sp. isolated from a soil sample collected in Japan [29]. This work reported wakodecalines A, B, two new tricyclic decalin derivatives with a spiro pentanone ring (C) and N-methylated terminal serine moiety as well as phomasetin, a known decalin compound with a terminal tetramic acid function [29].…”
Section: Discussionmentioning
confidence: 99%
“…isolated from a soil sample collected in Japan [29]. This work reported wakodecalines A, B, two new tricyclic decalin derivatives with a spiro pentanone ring (C) and N-methylated terminal serine moiety as well as phomasetin, a known decalin compound with a terminal tetramic acid function [29]. The lack of any other investigation in the literature on chemical constituents or biological activity has initiated our interest into this unexplored fungal taxon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation